UWB/GNSS-based cooperative positioning method for V2X applications - Gao, Yang; Meng, Xiaolin; Hancock, Craig; Stephenson, Scott; Zhang, Qiuzhao (2014)
Limited availability of GNSS signals in urban canyons is a challenge for the implementation of many positioning-based traffic safety applications, and V2X technology provides an alternative solution to resolve this problem. As a key communication component in V2X technology, Dedicated Short Range Communication (DSRC) not only allows vehicles to exchange their position, but also traffic safety related information such as real-time congestion, up-to-date accident details, speed limits, etc. This position and traffic information could underpin various traffic safety applications - for instance, lane departure warnings, potential collision avoidance, and traffic congestion warnings. By taking advantage of DSRC, a vehicle in a GNSS denied environment is able to calculate its position using the assistance of other vehicles with sufficient GNSS signals to fix their locations. The concept of cooperative positioning, which is also called collaborative positioning, has been proposed to achieve this goal.